2010
DOI: 10.1002/jcb.22581
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Importin α/β‐recognized nuclear localization signal in β‐dystroglycan

Abstract: Beta-dystroglycan (beta-DG) is a widely expressed transmembrane protein that plays important roles in connecting the extracellular matrix to the cytoskeleton, and thereby contributing to plasma membrane integrity and signal transduction. We previously observed nuclear localization of beta-DG in cultured cell lines, implying the existence of a nuclear targeting mechanism that directs it to the nucleus instead of the plasma membrane. In this study, we delineate the nuclear import pathway of beta-DG, characterizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 55 publications
(113 reference statements)
2
37
0
Order By: Relevance
“…In order to test more rigorously a role for dystroglycan in the nucleus we used a construct comprising an n-terminal myristoyl-tag, dystroglycan cytoplasmic domain and c-terminal GFP tag (Myr-cβDG-GFP23). We hypothesised that such a construct should effectively mimic the properties of 31 kDa fragment of dystroglycan in that it is membrane associated, contains the complete cytoplasmic domain sequence including NLS24 and it has a GFP tag to allow efficient visualisation and cell sorting (Figure 5ABC). Furthermore this construct was efficiently translocated to the nucleus without additional stimulation with androgens thus allowing any transcriptional response to dystroglycan alone to be detected without the high background of an androgen-mediated transcriptional response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to test more rigorously a role for dystroglycan in the nucleus we used a construct comprising an n-terminal myristoyl-tag, dystroglycan cytoplasmic domain and c-terminal GFP tag (Myr-cβDG-GFP23). We hypothesised that such a construct should effectively mimic the properties of 31 kDa fragment of dystroglycan in that it is membrane associated, contains the complete cytoplasmic domain sequence including NLS24 and it has a GFP tag to allow efficient visualisation and cell sorting (Figure 5ABC). Furthermore this construct was efficiently translocated to the nucleus without additional stimulation with androgens thus allowing any transcriptional response to dystroglycan alone to be detected without the high background of an androgen-mediated transcriptional response.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore this construct was efficiently translocated to the nucleus without additional stimulation with androgens thus allowing any transcriptional response to dystroglycan alone to be detected without the high background of an androgen-mediated transcriptional response. In order to compare the effects of nuclear targeting on transcription, we designed a construct (Myr-cβDGΔNLS-GFP) mutated in the NLS1424 to prevent translocation to the nucleus. Immunofluorescence analysis of LNCaP cells transiently transfected with these constructs and enriched by FACS (Supplementary Figure 1) demonstrated that whilst Myr-cβDG-GFP had both plasma membrane and nuclear localisation, Myr-cβDGΔNLS-GFP had only membrane (and Golgi) localisation, with no nuclear localisation (Figure 5D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a functional NLS in the cytoplasmic tail of β-dystroglycan was identified [63], which makes it plausible to propose that Dp71 gains access to the nucleus through its association with β-dystroglycan. Finally, it is noteworthy that a Dp71f-like protein was observed in the mitochondria of mdx and mdx 3cv mice [64].…”
Section: Nuclear Localization Of Dp71 and Dapc Componentsmentioning
confidence: 99%
“…Due to the presence of a conventional nuclear localization sequence (NLS)-/Imp-dependent nuclear import pathway in the cytoplasmic juxtamembrane region of β-Dg [87], β-Dg and proteolytic fragments containing the nuclear localization signal can be targeted to the nucleus via an importin-dependent pathway [88], where it can exert efects on nuclear architecture [89].…”
Section: Dg and Its Postranscriptional Modiicationsmentioning
confidence: 99%